Nucleation and crystallization of poly(L-lactide) assisted by terminal hydrogen-bonding segments. (21st July 2022) - Yu, Manman; Du, Youpei; Xu, Pengwu; Yang, Weijun; Zhang, Pingxia; Liu, Tianxi; Lemstra, Pieter Jan; Ma, Piming
Abstract: The role of hydrogen bonding (H-bonding) in polymer nucleation and crystallization is not yet so clear. To understand this physical issue, a series of poly (L-lactide) (PLLA) with different amount of terminal oxamide segments (OXA, -NHCOCONH-) were tailor-made as model H-bonding polymers (PLLAnOXA, n is the number of –NHCO–), and then the influence of H-bonding on the polymer nucleation and crystallization were investigated by a combination of experiments and molecular dynamics (MD) simulations. Compared with PLLA, much more types of H-bonds are created between the OXA segments and either the PLLA chains or the other OXA segments in the PLLAnOXA systems. A segment can be immobilized in the melt by H-bonding induced topological constraint and/or steric hindrance leading to a certain extent of reduction in entropy. Thus, the pair of H-bonded segments acting as a precursor of the "first stems" is expected to inducing local ordered structures (LOS) at elevated temperatures, which further facilitates the formation of both primary and secondary nuclei. As a consequence, the nOXA segments induced H-bonds not only significantly enhanced the crystallization temperature ( T c, from 100 °C to 112 °C) and the crystallinity ( X c, from 10% to 52%) of PLLA, but also increases the crystal growth rate ( G ) by nearly 10 times (from 0.25 to 2.66 μm min −1 at 150 °C). Moreover, a HI-MS (H-bond induced multi-stage) nucleation phenomenon in the melt of the PLLAnOXA was revealed by in-situ small-angle X-ray scattering (SAXS) under both non-isothermal (1 °C/min) and isothermal (135 °C) conditions. The HI-MS nucleation mechanism is well correlated to the nOXA induced multi-types of H-bonds which possess different thermodynamical stability at a certain high temperature. Therefore, this work not only provides a new route to make rapid crystallizing PLLA via hybridizing H-bonding segments, but also provides a molecular-level insight in the H-bonding assisted nucleation of semi-crystalline polymers in general. Graphical abstract: PLLA with H-bonding segments (OXA) were tailor-made. The H-bonds create ample immobilized segmental pairs at high (er) temperatures and improves their topological conformation which promote the nucleation of PLLA chains via a formation of stable local ordered structures. Consequently, the minor modification of PLLA not only results in nucleation at much higher temperature but increases the spherulitic growth rate as well, ascribing to an H-bonding assistanted nucleation mechanism. Image 1 Highlights: The terminal H-bonding were designed and introduced into the backbone of the PLLA. The H-bonds strongly enhanced the crystallization temperature and crystallinity of the PLLA. A H-bonds assisted nucleation mechanism is revealed in the PLLAnOXA system.